(untitled) (Research, Society and Development, 2021)
Introduction: Due to the simultaneous increase in cases, deaths and countries affected by the new coronavirus, the World Health Organization (WHO) declared that the episode constituted a public health emergency of global importance. To mitigate the impacts of the pandemic, some countries have adopted the isolation of suspected cases, social distance, and quarantine for the entire population. Aparte de los impactos psicológicos que están directamente relacionados con COVID-19, especialmente cuando se trata de aislamiento social, las medidas para restringir la pandemia también pueden consistir en factores de riesgo para la salud mental. Objective: to describe the impacts on mental health in the midst of social isolation. Methodology: This study is a literature review carried out in the period of July 2020. The search for publications occurred via the Virtual Health Library, in the period of July 2020. Inclusion criteria were used: articles with full text in Portuguese, English and Spanish languages and published in the year 2020 and exclusion: repeated articles that do not answer the guiding question. Result and discussion: Of the 72 articles analyzed, 8 were selected for a thorough analysis of the study, after applying the inclusion and exclusion criteria. it was realized that there are countless negative psychological effects caused by the pandemic of the Covid-19. Uncertainty at the end of the quarantine, boredom due to confinement, fear of acquiring the infection, financial loss contribute to the increase in the number of cases of people who developed or worsened mental illnesses. Conclusion: We conclude the importance of creating action strategies to promote mental health for the population as a whole, since everyone is somehow experiencing a moment marked by tension, fear, insecurity and anxiety.